Cerebellar Kv3.3 potassium channels activate TANK-binding kinase 1 to regulate trafficking of the cell survival protein Hax-1 - Zhang, Yalan; Varela, Luis; Szigeti-Buck, Klara; Williams, Adam; Stoiljkovic, Milan; Šestan-Peša, Matija; Henao-Mejia, Jorge; D’Acunzo, Pasquale; Levy, Efrat; Flavell, Richard A.; Horvath, Tamas L.; Kaczmarek, Leonard K. (Nature communications, 2021)
Mutations in KCNC3 , which encodes the Kv3.3 potassium channel, cause degeneration of the cerebellum, but exactly how the activity of an ion channel is linked to the survival of cerebellar neurons is not understood. Here, we report that Kv3.3 channels bind and stimulate Tank Binding Kinase 1 (TBK1), an enzyme that controls trafficking of membrane proteins into multivesicular bodies, and that this stimulation is greatly increased by a disease-causing Kv3.3 mutation. TBK1 activity is required for the binding of Kv3.3 to its auxiliary subunit Hax-1, which prevents channel inactivation with depolarization. Hax-1 is also an anti-apoptotic protein required for survival of cerebellar neurons. Overactivation of TBK1 by the mutant channel leads to the loss of Hax-1 by its accumulation in multivesicular bodies and lysosomes, and also stimulates exosome release from neurons. This process is coupled to activation of caspases and increased cell death. Our studies indicate that Kv3.3 channels are directly coupled to TBK1-dependent biochemical pathways that determine the trafficking of cellular constituents and neuronal survival. How the activity of the neuronal Kv3.3 voltage-dependent channel is regulated is unclear. Here, the authors show that the known Kv3.3 channel complex with Hax1, which affects spinal cerebellar ataxia, regulates the enzyme Tank Binding Kinase 1, modulating survival of cerebellar neurons.